Harnessing biological nitrogen fixation in African agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
proceedings of the 6th International Conference of the African Association for Biological Nitrogen Fixation held in Harare in September 1994, have been published by University of Zimbabwe Publications with CTA's support. 270 pp. ISBN 0 908307 58 6